Copper promotes TFF1-mediated Helicobacter pylori colonization. - Sandro Montefusco; Roberta Esposito; Luca D'Andrea; Maria Chiara Monti; Ciara Dunne; Brendan Dolan; Alessandra Tosco; Liberato Marzullo; Marguerite Clyne (PLoS ONE, 2013)
The trefoil peptides (TFF1, TFF2 and TFF3) are a family of small highly conserved proteins that play an essential role in epithelial regeneration within the gastrointestinal tract, where they are mainly expressed. TFF1 expression is strongly induced after mucosal injury and it has been proposed that tff1 functions as a gastric tumor suppressor gene. Several studies confirm that tff1 expression is frequently lost in gastric cancer because of deletions, mutations or methylation of the tff1 promoter. Infection by Helicobacter pylori (H. pylori) results in chronic gastritis and it can lead to the development of gastric or duodenal ulcers. Moreover, it is known that there is a strong link to the development of gastric cancer. It has been shown that H. pylori interacts with the dimeric form of TFF1 and that the rough form of lipopolysaccharide mediates this interaction. We have previously reported that the carboxy-terminus of TFF1 is able to specifically bind copper ions (Cu) and that Cu binding favours the homodimerization of the peptide, thus enhancing its motogenic activity. Here, we report that the Cu-TFF1 cuprocomplex promotes adherence of H. pylori to epithelial cells. Adherence of H. pylori to gastric adenocarcinoma cells, AGS AC1 cells, induced to hyper-express TFF1 was enhanced compared to noninduced cells. Copper further promoted this interaction. A H. pylori mutant unable to bind TFF1 did not show enhanced infection of induced cells. Cu treatment induced a thickening of the mucus layer produced by the colorectal adenocarcinoma mucus secreting, goblet cells, HT29-E12 and promoted H. pylori colonisation. Finally, SPR analysis shows that the C-terminus of TFF1, involved in the binding of copper, is also able to selectively bind H. pylori RF-LPS.